2006
DOI: 10.1002/jemt.20288
|View full text |Cite
|
Sign up to set email alerts
|

HRTEM of dislocation cores and thin‐foil effects in metals and intermetallic compounds

Abstract: Examples of the observation and analysis of dislocation cores and dislocation fine structure in metals and intermetallics using high resolution transmission electron microscopy are discussed. Specific examples include the 60 degrees dislocations in aluminum, a011 edge dislocations in NiAl, and screw dislocations in Ni3Al. The effect of the thin TEM foils on the structure and imaging of these dislocations is discussed in light of embedded atom method calculations for several configurations and coupled with imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 53 publications
0
6
1
Order By: Relevance
“…Their calculations matched those found experimentally, where the screw type dislocation had a much narrower stacking fault width than the edge type dislocation. Indeed, in pure FCC metals, dissociation distances do not vary greatly among dislocations with similar orientation, supporting the idea of a global SFE; however, a significant difference in stacking fault widths is common among different orientations.The average range in separation distances observed in pure FCC alloys, from the studies mentioned above, was found to bearound ±0.45nm [35,[37][38][39], which is almost an order of magnitude less than the range found in the present study (± 3.4nm). In the present study, the distance between individual ½<110>dislocations in the arrays is on the order of several hundred nm.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Their calculations matched those found experimentally, where the screw type dislocation had a much narrower stacking fault width than the edge type dislocation. Indeed, in pure FCC metals, dissociation distances do not vary greatly among dislocations with similar orientation, supporting the idea of a global SFE; however, a significant difference in stacking fault widths is common among different orientations.The average range in separation distances observed in pure FCC alloys, from the studies mentioned above, was found to bearound ±0.45nm [35,[37][38][39], which is almost an order of magnitude less than the range found in the present study (± 3.4nm). In the present study, the distance between individual ½<110>dislocations in the arrays is on the order of several hundred nm.…”
Section: Discussioncontrasting
confidence: 73%
“…Previous studies using weak beam imaging techniques have been able to accurately deduce SFE energies in pure FCC metals through direct observation of ½<110> dislocation dissociation distances [35][36][37]31]. Both Carter et al and Mills et al did not find a large variation in dissociation distances between dislocations of similar orientation [35,37]. In 1971, Cocknayeet al recorded the first experimental observations that dissociation distances in FCC Ag differed depending on the orientation of the dislocation, where screw types exhibited the smallest separation and edge types the largest [38].…”
Section: Discussionmentioning
confidence: 99%
“…(16). Equation (8) describes the relation between v and σ and T in the thermally activated regime. The functional form for H KP given by Eq.…”
Section: Discussionmentioning
confidence: 99%
“…However, experimental measurements concerning single dislocation properties are exceedingly difficult, and only recently have experimental techniques reached a level of resolution capable of isolating individual dislocation behavior, 7,8 such as in bcc Fe. 9 Consequently, a wealth of atomistic simulation studies have been performed over the last decade or so in an attempt to shed light on dislocation structure and core properties and energetics.…”
Section: Introductionmentioning
confidence: 99%
“…A potential advantage of the proposed model is that it may be applied to predict τ p for structures whose interatomic potentials are not available, as long as their dislocation core structures can be characterized experimentally with sufficient accuracy. Considering the rapid development of advanced experimental techniques such as aberration corrected high resolution transmission electron microscopy, characterization of dislocation core with sufficient accuracy could be expected in the near future [34]. In this scenario, the gradient coefficient λ shall be determined by calibrating the predicted profile against the ones measured experimentally, and the γ-GSF surface would be computed via DFT calculations [13], therefore the proposed model has the potential to be applied to more complex crystal structures.…”
mentioning
confidence: 99%